THE EFFECT OF CONSUMER PURCHASING POWER ON VALUE ADDED TAX (PPN) IMPLICATIONS ON SALES TAX ON LUXURY GOODS (PPNBM): (Survey on Electronics Consumers at Informa Elektronik PIM Palembang) - Mayang Sari; Lesi Hertati; Vhika Meiriasari (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
This study aims to determine the effect of consumer purchasing power on the implications of value-added tax (VAT) for sales tax on luxury goods (PPnBM). The research population consisted of consumers at Informa Elektronik PIM Palembang, and the research sample was determined using the Slovin formula method. This study falls under the category of quantitative research. The data analysis employed in this study includes descriptive analysis, multiple linear regression analysis, preceded by an analysis of the F-test and t-test, and an analysis of the coefficient of determination (R2). The results of the study indicate that the Consumer Purchasing Power variable has a significant effect on Sales Tax on Luxury Goods (PPnBM). Furthermore, the Value Added Tax (VAT) variable also shows a significant effect on Sales Tax on Luxury Goods (PPnBM).